Erratum to: Search for new physics in dijet angular distributions using proton-proton collisions at s = 13 TeV and constraints on dark matter and other models (The European Physical Journal C, (2018), 78, 9, (789), 10.1140/epjc/s10052-018-6242-x) - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Valle, A. Escalante Del; Flechl, M.; et al. (My University, 2022)
In this article the author name Luigi Calligaris was incorrectly written as A. Calligaris. The original article has been corrected.